Describing Spiritual Growth in an Online Religious Education Course. Issue 1 (2nd January 2018) - Fryar, Ben; Wilcox, Brad; Hilton, John; Rich, Peter J.
ABSTRACT: This research examined the phenomenon of spiritual growth in students taking an online religious education course at Brigham Young University–Idaho. Semi-structured interviews were conducted with 10 students who reported positive gains in spirituality as a result of the course. Students described their experience in the online course and the factors that contributed to their success. Results suggest participants took a great deal of ownership in their own spiritual growth. Although it seems likely participants were already highly self-directed, aspects of the online experience appeared to encourage self-direction. The course design was flexible enough for research participants to explore ideas on their own while also being structured enough to provide a guided experience. Online instructors acted as guides and facilitators, playing a less prominent role than face-to-face instructors. Frequent engagement in and reflection through writing appeared to be important for students' spiritual growth, whereas online interactions with other students seemed to have minimal impact. However, some responses suggested online interaction with peers was an area with potential for greater influence.